HybriDFEM and FEM Numerical Framework for the Structural Analysis of Impact-loaded Unreinforced Masonries - Castro Osorio, Mariana; Oudah, Allachen (My University, 2026)
Unreinforced masonry walls constitute a significant portion of Sweden’s built environ- ment, yet their resistance to out-of-plane impact loading remains poorly understood and inade quately covered by existing design guidelines. This thesis develops and validates two in dependent numerical frameworks for simulating the dynamic response of double- wythe URMwalls subjected to pendulum impact loading: a continuum finite element model imple mented in Abaqus/Explicit, and a Hybrid Discrete–Finite Element Method (HybriDFEM) model. Both adopt a meso-scale modelling strategy and are calibrated against quasi-static four-point bending tests before being validated against three exper- imental impact cam paigns conducted at RISE Research Institutes of Sweden. The results demonstrate that both frameworks reproduced the global dynamic response, in cluding out-of-plane displacements, impact forces, arching behaviour, wall uplift, and lo cal failure mechanisms. The Abaqus model shows better agreement for low-mass, low velocity configurations and provides a detailed reference for local stress and damage devel opment, while HybriDFEM performs consistently across a broader range of impact energies at substantially lower computational cost. Together, the two frameworks provide comple mentary tools for the assessment of URM walls under impulsive loading, and their multi campaign validation, including a blind prediction, contributes to the ongoing RISE–FORTV programme on design guidelines for masonry structures subjected to blast and impact load ing.
Keywords: Unreinforced masonry, out-of-plane impact, Abaqus/Explicit, HybriDFEM, meso-scale modelling, dynamic response, arching action, experimental validation, blind pre diction